2003
DOI: 10.1095/biolreprod.103.016501
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Characterization of a Transgenic Mouse with a Functional Human TSPY1

Abstract: To generate an animal model that is suitable for the analysis of regulation and expression of human testis-specific protein, Y-encoded TSPY, a transgenic mouse line, TgTSPY9, harboring a complete structural human TSPY gene was generated. Fluorescence in situ hybridization and Southern analyses show that approximately 50 copies of the human TSPY transgene are integrated at a single chromosomal site that maps to the distal long arm of the Y chromosome. The transgene is correctly transcribed and spliced according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
56
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(62 citation statements)
references
References 32 publications
6
56
0
Order By: Relevance
“…2B,C). These expression patterns are similar to that of a transgenic line harboring a human TSPY transgene on the Y chromosome of the host (Schubert et al, 2003). …”
supporting
confidence: 59%
See 2 more Smart Citations
“…2B,C). These expression patterns are similar to that of a transgenic line harboring a human TSPY transgene on the Y chromosome of the host (Schubert et al, 2003). …”
supporting
confidence: 59%
“…This latter observation suggests that the Tspy gene might be active in the spermatids of the rodents. If the regulatory mechanism in the rat is preserved in the mouse, our results suggest that the 2.4-kb human promoter is properly regulated in the spermatids of transgenic mice.Studies on TSPY expression, initially postulated to be testis-specific, in the brain are somewhat limited, despite the fact that transcripts of the human TSPY transgene could be detected by the Northern hybridization technique (Schubert et al, 2003) and TSPY ESTs have also been reported in databases of brain cDNA libraries (GenBank access. nos.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another study suggested that the SV40 large T antigen oncogene directed by a 1.3-kb human TSPY promoter was capable of inducing tumor formation in the pituitary gland of the host [49]. Other transgenic mice harboring multiple copies of a 8.2-kb human TSPY DNA showed a spermatogonia/spermatocytes specific expression of the transgene, similar to the human TSPY expression pattern [50]. Although the respective transgene expression could be influenced by the length of the promoter, integration sites and genetic background of the hosts, it is conceivable that a combination of species-specific cis and trans-elements are important for the differential expression of the endogenous hTSPY and rTspy in respective types of germ cells.…”
Section: Discussionmentioning
confidence: 94%
“…The human TSPY promoter is subjected to methylation that regulates its expression in certain cancer cells [48]. Despite such differences between the promoters of the rat Tspy and human TSPY, the exact mechanism(s) of their differential expression patterns cannot be unambiguously defined since various transgenic mouse studies showed variation of transgene expression patterns by the human TSPY promoter [18,49,50]. Transgenic mice harboring a human 2.4-kb TSPY promoter directed reporter gene showed a preferential transgene-expression in spermatids of the testis, similar to the rTspy expression pattern in the present study [18].…”
Section: Discussionmentioning
confidence: 99%